1991
DOI: 10.1063/1.460807
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation spectroscopy of benzene cluster ions: (C6H6)+2 and (C6H6)+3

Abstract: The photodissociation of size-selected benzene cluster ions, (C6H6)+m+hω→(C6H6)+n+ (m−n)C6H6, has been investigated in the 410–750 nm wavelength range using tunable dye laser radiation. The measurements were performed using a tandem mass spectrometer [a linear time-of-flight (TOF)/reflectron TOF] combined with multiphoton ionization (MPI) for ion preparation. Only C6H+6 was detected as a photofragment of (C6H6)+2 and (C6H6)+3, while both C6H+6 and (C6H6)+2 fragments were observed in the case of (C6H6)+4 photod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 45 publications
3
54
1
Order By: Relevance
“…The results of (C 6 H 6 ) 3 + as well as (C 6 H 6 ) 2 + have already been reported and discussed in our previous publication. 8 When the (C 6 H 6 ) n + ions with n ) 4-6 were photodissociated in this wavelength region, both C 6 H 6 + and (C 6 H 6 ) 2 + were mainly detected as photofragment ions. We confirmed that the yield of each fragment ion showed almost linear dependence on the laser power.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of (C 6 H 6 ) 3 + as well as (C 6 H 6 ) 2 + have already been reported and discussed in our previous publication. 8 When the (C 6 H 6 ) n + ions with n ) 4-6 were photodissociated in this wavelength region, both C 6 H 6 + and (C 6 H 6 ) 2 + were mainly detected as photofragment ions. We confirmed that the yield of each fragment ion showed almost linear dependence on the laser power.…”
Section: Resultsmentioning
confidence: 98%
“…The sums of the normalized yields of fragment ions, C6H6 + and (C6H6)2 + , are plotted against the wavelengths of the dissociation laser. The spectra for n ) 2 and 3 are already reported in our previous work 8. Two local excitation (LE) bands are commonly observed for all the cluster ions.…”
mentioning
confidence: 90%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The dimer ion form is kept as a dimer ion core in some homo-molecular cluster ions, such as (benzene) n + . 13,14 However, the charge distribution of cluster ions is not predictable so easily on the basis of IE, PA, or EA. One curious manner on the charge distribution occurs for (CO 2 ) n − cluster anions, 16,20,21 which show switching of the ion core between n = 6 and 7 and between 13 and 14.…”
Section: Introductionmentioning
confidence: 99%
“…46,47 Benzene clusters are the simplest prototype aromatic molecules for understanding the fundamental aspects of -interactions. An extensive amount of work has hitherto been devoted to the spectroscopy and structure of neutral and cationic clusters of benzene; 7,8,22,[57][58][59][60][61][62][63][64][65][66][67][68][69][70] however, there has been, to the best of our knowledge, no report on anionic clusters of benzene. As is well known, a benzene molecule has a negative electron affinity (EA); for example, vertical EA = À1:12 eV has been reported by electron transmission spectroscopy.…”
Section: Experimental Methodologymentioning
confidence: 99%